The Determinants of Competitiveness of the Jordanian Banking Sector (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study aimed to analyze the determinants of competitiveness in Jordan’s banking sector and assess the impact of each force on domestic banking performance through enhancing Porter’s Five Forces model through the addition of a sixth force—the role of the Central Bank. Employing both descriptive and analytical methods, the study found that the traditional five forces do not present a significant threat to Jordanian banks, which have maintained their market share despite the entry of foreign competitors, largely due to customer loyalty and advanced banking services. The Central Bank was shown to play a supportive role in promoting competitiveness, justifying its inclusion as a critical additional force in the analytical model. The findings revealed a notable decline in banking concentration between 2008 and 2021, indicating a more competitive market environment. This improvement was reflected in Jordan’s rise in the 2024 Global Competitiveness Index. The study recommends implementing policies to reduce operational costs, reform banking regulations, enforce anti-trust laws, encourage innovation, and enhance banking service quality to boost competitiveness and attract foreign investment.
Keywords: Competitiveness; Porter’s Model; Jordanian Banks